2014
DOI: 10.5539/ijps.v6n4p115
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Resiliency and Life Satisfaction in High School-Aged Students in Belize

Abstract: This study assesses resiliency and life satisfaction of high school youth from Belize. Due to the contrast of geography, culture, and economic characteristics, between Belize and the U.S. many differences were hypothesized to be found. Resiliency and life satisfaction were hypothesized (a) to be lower in the youth from Belize when compared with previous studies of youth conducted in the United States, (b) youth in Belize, who have high resilience, will also have high life satisfaction and (c) youth who has low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Additionally, according to the COR theory, at times of stress people make an effort to protect their SWB via retaining and enhancing their personal resources [20,21]. In line with the results of previous studies among various populations, e.g., [44,[46][47][48]50], our findings indicate that personal resources-specifically, self-esteem and sense of mastery-contributed to increased life satisfaction among the young backpackers. Moreover, our results also show that personal resources contributed to social support and community participation, which functioned as mediating variables that, in turn, also promoted increased life satisfaction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, according to the COR theory, at times of stress people make an effort to protect their SWB via retaining and enhancing their personal resources [20,21]. In line with the results of previous studies among various populations, e.g., [44,[46][47][48]50], our findings indicate that personal resources-specifically, self-esteem and sense of mastery-contributed to increased life satisfaction among the young backpackers. Moreover, our results also show that personal resources contributed to social support and community participation, which functioned as mediating variables that, in turn, also promoted increased life satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Self-esteem refers to the individual's self-image, which is based on self-evaluations about appearance, aspirations, and the ability to cope with challenges [41,42]. Although many studies have shown that selfesteem is positively associated with life satisfaction, e.g., [43][44][45][46], few have examined the association between a sense of mastery and life satisfaction in different populations [47,48] and specifically among adolescents [49,50]. One study conducted among young adults did indicate that proactive coping, a variable that is similar to a sense of mastery, was related to life satisfaction [51].…”
Section: Personal Resourcesmentioning
confidence: 99%
“…According to Diener (2000), because of all these reasons, the individuals with these personality traits are more resilient, stronger and happier than other individuals both in their social lives and in their professional lives. Hence, there are many studies revealing that psychological resilience affects job satisfaction and thus, job performance (Basım & Çetin, 2011;Smith & Smith, 2015;Rani & Midha, 2014;Youngblom et al, 2014;Batan & Ayten, 2015;Tümlü & Recepoğlu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Masten dan Barnes (Masten & Barnes, 2018) menyatakan bahwa resiliensi adalah kapasitas suatu sistem untuk mampu beradaptasi dengan tantangan yang mengancam pada suatu fungsi perkembangan maupun kelangsungan hidup, yang menjadikan individu lebih tangguh (Youngblom et al, 2014). Ia menjadi bagian dari aspek intrapersonal well-being (Kurniastuti & Azwar, 2014), yang berarti individu memiliki kapabilitas untuk menghadapi masalah-masalah yang ada secara resisten.…”
Section: Resiliensi Learning Dan Growth Mindsetunclassified